EHXI: a permanently installed, hard x-ray imager for the National Ignition Facility. (14th June 2016) - Döppner, T.; Bachmann, B.; Albert, F.; Bell, P.; Burns, S.; Celeste, J.; Chow, R.; Divol, L.; Dewald, E.L.; Hohenberger, M.; Huntington, C.M.; Izumi, N.; et al.
Abstract: We have designed and built a multi-pinhole imaging system for high energy x-rays ( ⩾ 50 keV) that is permanently installed in the equatorial plane outside of the target chamber at the National Ignition Facility (NIF). It records absolutely-calibrated, time-integrated x-ray images with the same line-of-sight as the multi-channel, spatially integrating hard x-ray detector FFLEX [McDonald et al., Rev. Sci. Instrum. 75 (2004) 3753 ], having a side view of indirect-drive inertial confinement fusion (ICF) implosion targets. The equatorial hard x-ray imager (eHXI) has recorded images on the majority of ICF implosion experiments since May 2011. eHXI provides valuable information on hot electron distribution in hohlraum experiments, target alignment, potential hohlraum drive asymmetries and serves as a long term reference for the FFLEX diagnostics.